2020
DOI: 10.1002/tox.23051
|View full text |Cite
|
Sign up to set email alerts
|

Chemomodulatory effect of neferine on DMBA‐induced squamous cell carcinogenesis: Biochemical and molecular approach

Abstract: Background Neferine (NEF) is nontoxic, bisbenzylisoquinoline alkaloid is derived from the seed embryo of lotus, a familiar medicinal plant. Although several mechanisms have been planned, an evident antitumor action pathway of NEF on the oral tumor is still not known. In the current study, we aimed at investigating the protecting effect of NEF against experimental oral carcinoma and clarify its possible mechanism through the induction of apoptosis, proliferation, and inflammatory signaling pathways. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Our results showed evidence of fibrous connective tissue infiltrated with moderate inflammatory cells in the cheek pouches of animals treated with DMBA for 6 weeks (positive control group, Fig. 3) as reported in similar studies [1,10,[16][17][18][19]. Shahzad et al (2009) reported that intraperitoneal administration of black seed oil caused significant reduction in all markers of allergic inflammation by inhibiting delayed hypersensitivity and T-cell proliferation in the spleen [22].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results showed evidence of fibrous connective tissue infiltrated with moderate inflammatory cells in the cheek pouches of animals treated with DMBA for 6 weeks (positive control group, Fig. 3) as reported in similar studies [1,10,[16][17][18][19]. Shahzad et al (2009) reported that intraperitoneal administration of black seed oil caused significant reduction in all markers of allergic inflammation by inhibiting delayed hypersensitivity and T-cell proliferation in the spleen [22].…”
Section: Discussionsupporting
confidence: 87%
“…ab Indicate that a significant difference (P value < 0.05) exists between compared sub/groups that are marked with the same letter. The DMBA-treated animals (GII) showed severe dysplasia, as documented in similar studies [1,10,[16][17][18][19][20]. This was accompanied by a significant reduction in total WBCs and lymphocytes counts as compared to untreated healthy controls (GI), which indicates the high level of local and systemic toxicity of DMBA.…”
Section: Discussionmentioning
confidence: 58%
“…For studying on dysplastic lesions in vivo, the only ethical way was induction of dysplasia in animals. Standing on the shoulders of previous studies, we found out that the most appropriate way is induction of dysplasia by painting DMBA on hamsters’ buccal pouch (14,15). We even did not trust immediately and designed a pilot study to evaluate the rate of induction of dysplasia (13); but in this study, we encountered two problems: in spite of considering standard protocols in housing our hamsters, we encountered a rather high number of dead specimens.…”
Section: Discussionmentioning
confidence: 99%
“…All hamsters were sacrificed using over dose of Zoletil 50/Zolazepam (0.5 mg kg −1 ) after finishing their own period of irradiation (10 hamsters were sacrificed after receiving four sessions of 810 nm laser which lasted 8 days totally; other 10 hamsters were sacrificed after receiving four sessions of 660 nm laser which took place in 8 days, eight hamsters were sacrificed after receiving 12 sessions of 660 nm laser which lasted 30 days totally; and 11 of them which received 810 nm laser for 12 sessions were sacrificed after 30 days). For histopathologic study of the tissue, we used light microscopes, while samples had been fixed in 10% formalin, dehydrated in high concentrate alcohol and cleared by xylene and finally soaked in paraffin (14,15).…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear factor-κappa B (NF-κB), a protein complex consisting of five transcription factors, namely RelA, RelB, c-Rel, NF-κB1, and NF-κB2, has been reported to play an important role in cell proliferation and survival in HNSCC [ 62 , 63 ]. Preclinical studies using HNSCC models have demonstrated the inhibition of NF-κB, leading to apoptosis with neferine, trichodermin, cinnamaldehyde, and Seco-A -ring oleanane [ 48 , 50 , 64 , 65 ].…”
Section: Chemotherapeutic Properties Of Natural Products On Essential...mentioning
confidence: 99%